Factors affecting the rumen fluid foaming performance in goat fed high concentrate diet - Tan, Zehao; Liu, JunFeng; Wang, Lizhi (Frontiers in Veterinary Science, 2024)
Feeding high concentrate diets is highly prone to rumen bloat in ruminants, which is very common in production. This study explored the factors responsible for the occurrence of foamy rumen bloat. The experiment was conducted using goats as test animals, fed high concentrate diets and scored for rumen distension into high, medium and low bloat score groups. Rumen fluid was collected from 6 goats in each group separately. The foaming production, foam persistence, pH value, viscosity and the content of protein, total saccharide and mineral elements in rumen original fluid (ROL) were measured, and the protein and total saccharide content in rumen foam liquid (RFL) and rumen residual liquid (RRL) were determined. The results showed that the protein content in rumen original fluid and rumen foam liquid was significantly higher than that in rumen residual liquid (p < 0.05), and the protein content in rumen foam liquid was 10.81% higher than that in rumen original fluid. The higher the rumen bloat score, the higher the foam production, foam persistence, viscosity, protein, Ni, Mg, Ca, and K concentrations of the rumen original fluid, and the lower the PH and Na concentrations of the rumen original fluid; correlation analysis showed that the viscosity of the rumen original fluid was significantly and positively correlated with the foam production and foam persistence (p < 0.05). Foaming production and foam persistence of rumen original fluid were significantly and positively correlated with the contents of protein, total saccharide, K, Ca, Mg and Ni (p < 0.05). and negatively correlated with the content of Na (p < 0.05); after controlling other components those were significantly related to the foaming performance of rumen original fluid only protein still was significantly positively correlated with the foam persistence of rumen original fluid (P<0.05). In summary, the contents of protein, total saccharide and mineral elements in the rumen fluid had a significant effect on the foaming performance of rumen in ruminants, with protein playing a decisive role and the other components playing a supporting role. Reducing the content of protein in the diet in production is beneficial to reduce the occurrence of rumen bloat in ruminants.